Changes of factors associated with vaccine hesitancy in Chinese residents: A qualitative study - Long, Sigui; Wu, Jingying; Wang, Shile; Zhao, Yaqi; Wang, Jianli; Zhao, Shuangyu; Niu, Qing; Jin, Hui (Frontiers in Public Health, 2022)
Introduction There is an urgent need to address vaccine hesitancy to achieve booster vaccination. This study aimed to reveal the factors associated with vaccine hesitancy (including COVID-19 vaccine) among Chinese residents, address modifications of the factors since the previous year, and propose vaccination rate improvement measures. Materials and methods This qualitative return visit study was performed between January and mid-February 2022, following the last interview conducted between February and March 2021. According to an outline designed in advance, 60 Chinese residents from 12 provinces participated in semi-structured interviews. Results Vaccine safety was the biggest concern raised by respondents, followed by self-immunity and vaccine effectiveness, eliciting concern since the interview last year. Notably, online media accounted for a more significant portion of suggestion sources than before, and fear of pain was a novel factor affecting vaccine hesitancy. Moreover, unlike other areas, those from provinces with a per capita gross domestic product of 3–5 (RMB 10,000) reported less concern about vaccine price and effectiveness. They tended to seek advice via online media less and were greatly influenced by vaccination policies. Conclusions Influential factors of vaccine hesitancy among Chinese residents are changing dynamically. Monitoring these trends is essential for public health measures and higher vaccination levels.